Clinical and genetic characterization of patients segregating variants in KPTN, MINPP1, NGLY1, AP4B1, and SON underlying neurodevelopmental disorders: Genetic and phenotypic expansion. Issue 8 (11th October 2022) - Ullah, Asmat; Shah, Abid Ali; Alluqmani, Majed; Haider, Nighat; Aman, Hasan; Alfadhli, Fatima; Almatrafi, Ahmad M.; Albalawi, Alia M.; Krishin, Jai; Ullah Khan, Fati; Anjam, Bilal Ali; Abdullah; et al.
Abstract: Neurodevelopmental disorders (NDDs) are heterogeneous genetic conditions of the central nervous system (CNS). Primary phenotypes of NDDs include epilepsy, loss of developmental skills, abnormal movements, muscle weakness, ocular anomalies, hearing problems, and macro‐ or microcephaly. NDDs occur due to variants in genes encoding proteins involved in the structure and function of CNS, thus interrupting its normal physiological role. In the study presented here, four consanguineous families (A–D), with members showing neurodevelopmental symptoms, were recruited for clinical and genetic characterization of the phenotypes. Clinical examinations, including Seguin Form Board Test (SFBT), Vineland Social Maturity Scale (VSMS), brain Magnetic Resonance Imaging (MRI), Electroencephalogram (EEG), Electromyography (EMG), Nerve Conduction Velocity (NCV), and Magnetic Resonance Spectroscopy, were employed to characterize the disease phenotypes. Whole exome sequencing (WES) followed by Sanger sequencing was employed to search for the genetic basis of the neurological symptoms observed in four families (A–D). Two of these families (A, B) were of Saudi Arabian origin, and two others (C, D) were of Pakistan origin. Two homozygous missense (KPTN: NM_007059.4:c.301T>G: NP_008990.2; p.(Phe101Val) and MINPP1:NM_001178118.2:c.1202G>A: NP_001171588.1; p.(Arg401Gln)) variants in families A and B, respectively, and two homozygous nonsense (NGLY1:NM_018297.3:c.1534_1541dup: NP_060767.2; p.(Ser515LysfsTer51) and AP4B1:NM_001253852:c.1668G>A: NP_001240781.1; p.(Trp556X)) variants in families C and D, respectively, were identified. Interestingly, additional heterozygous nonsense variant in SON: NM_138927.2: c.5753_5756del: NP_620305.3; p.(Val1918GlufsTer87) and a homozygous variant in FLG (FLG: NM_002016.2:c.7339C>T: NP_002007.1; p.(Arg2447X) were detected in families A and D, respectively. Further, we determined the deleteriousness of each variant through computational approaches. The present study expands the phenotypic and genetic spectrum of NDD‐associated genes (KPTN, MINPP1, NGLY1, and AP4B1). Moreover, additional nonsense variants (SON: c.5753_5756del and FLG: c.7339C>T) identified in two families segregating with the phenotype might explain the phenotypic variability and severity in our patients.